FFM facets and their relations with different forms of antisocial behavior: An expanded meta-analysis. (July 2018) - Vize, Colin E.; Miller, Joshua D.; Lynam, Donald R.
Abstract: Research examining the relation between personality and antisocial and aggressive behaviors has shown that traits related to antagonism and disinhibition are the most important correlates of such behaviors. However, much of this research has focused on personality at a higher-order level, such as the domain level within the Five Factor Model (FFM). The present meta-analysis specifically focused on the lower-order facet scales of the FFM (as measured by the NEO-PI-R and IPIP-NEO) which have been shown to add important predictive utility above the domains. Expanding on previous work, the current study examined the relations between the FFM facets and a variety of antisocial behaviors including physical aggression, relational aggression, reactive aggression, proactive aggression, and non-violent antisocial behavior. Meta-analytic results show that a subset of FFM facets, primarily those related to antagonistic and disinhibited behavior, showed the most consistent relations with antisocial behaviors. However, effect size magnitudes were influenced by what type of antisocial behavior was examined. The results are discussed within the broader context of research on personality and antisocial behavior, etiological models of aggressive behavior, and the degree to which the results match the trait profiles of constructs with robust links to antisocial behavior (i.e., psychopathy). Highlights: The present meta-analysis extends previous work that examining relations between Five Factor Model facets and antisocial behavior. The results show that facets of Agreeableness and Conscientiousness were consistently related to various antisocial and aggressive outcomes. Specific facets within broader domains also showed important relations with antisocial and aggressive behavior. Profile comparisons show that the FFM facet profiles of antisocial and aggressive behavior converge with FFM facet profiles of psychopathy.